2012
DOI: 10.1111/j.1460-6984.2012.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of ‘what’, ‘where’, ‘what house’ and other repair initiations in the home environment of hearing‐impaired individuals

Abstract: Through a deeper qualitative analysis, conversational research can provide extended knowledge of the occurrence and style of ordinary repair initiations and highlight their relationship in certain conversational environments. A robust starting point in communication therapy is increasing the awareness of HI individuals' existing skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 17 publications
(78 reference statements)
2
24
3
Order By: Relevance
“…Our findings on HA users with mild to moderately severe HL are in contrast with the previous findings of conversations involving participants with severe acquired HL using hearing amplification (e.g., Lind et al . , Pajo ). HA users with severe HL are found to make significantly more open‐class repair initiations than their interlocutors.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our findings on HA users with mild to moderately severe HL are in contrast with the previous findings of conversations involving participants with severe acquired HL using hearing amplification (e.g., Lind et al . , Pajo ). HA users with severe HL are found to make significantly more open‐class repair initiations than their interlocutors.…”
Section: Discussionmentioning
confidence: 99%
“…The studies found concerned only few participants, seven (Lind et al . ) and five (Pajo ), and the participants had severe HL. Similar studies on the conversational interactions of adults with mild to moderate HL were not found.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations